The Virtues of Understanding Makiyah and Madaniyah Verses in Human Life - Ramadhani, Nurul; Hidayat, Wahyu; Nuha, Farahah Kamilatun; Rahmawati, Siti (Jurnal Al Burhan, 2024)
The Qur'an was revealed to Prophet Muhammad SAW gradually as a guide to the path of the Apostle's da'wah in the cities of Mecca and Medina for 23 years. This article aims to find out the virtues of the Makiyah and Madaniyah verses in living with humans. From this article, researchers are intended to prove the wisdom of learning suras of the Qur'an, especially in the verses of Makiyah and Madaniyah. This research employed library research as the rsearch method. In conclusion, the primacy of the Makiyah and Madaniyya verses explains that the Makiyah verse was revealed in the city of Mecca for the purpose of punishment for the Meccans while the Madaniyya verse was revealed in the city of Medina as a legal explanation for the inhabitants of Medina. Besides that, The characteristics of the Makiyah and Madaniyah verses in Kitab al-Itqan fii ulumir Qur'an explain the geographical aspect based on the location of the verse.